Measuring disease progression in early Parkinson disease: the National Institutes of Health Exploratory Trials in Parkinson Disease (NET-PD) experience - Parashos, Sotirios A; Luo, Sheng; Biglan, Kevin M; Bodis-Wollner, Ivan; He, Bo; Liang, Grace S; Ross, G Webster; Tilley, Barbara C; Shulman, Lisa M (JAMA neurology, 2014)
Optimizing assessments of rate of progression in Parkinson disease (PD) is important in designing clinical trials, especially of potential disease-modifying agents. To examine the value of measures of impairment, disability, and quality of life in assessing progression in early PD. Inception cohort analysis of data from 413 patients with early, untreated PD who were enrolled in 2 multicenter, randomized, double-blind clinical trials. Participants were randomly assigned to 1 of 5 treatments (67 received creatine, 66 received minocycline, 71 received coenzyme Q10, 71 received GPI-1485, and 138 received placebo). We assessed the association between the rates of change in measures of impairment, disability, and quality of life and time to initiation of symptomatic treatment. Time between baseline assessment and need for the initiation of symptomatic pharmaceutical treatment for PD was the primary indicator of disease progression. After adjusting for baseline confounding variables with regard to the Unified Parkinson's Disease Rating Scale (UPDRS) Part II score, the UPDRS Part III score, the modified Rankin Scale score, level of education, and treatment group, we assessed the rate of change for the following measurements: the UPDRS Part II score; the UPDRS Part III score; the Schwab and England Independence Scale score (which measures activities of daily living); the Total Functional Capacity scale; the 39-item Parkinson's Disease Questionnaire, summary index, and activities of daily living subscale; and version 2 of the 12-item Short Form Health Survey Physical Summary and Mental Summary. Variables reaching the statistical threshold in univariate analysis were entered into a multivariable Cox proportional hazards model using time to symptomatic treatment as the dependent variable. More rapid change (ie, worsening) in the UPDRS Part II score (hazard ratio, 1.15 [95% CI, 1.08-1.22] for 1 scale unit change per 6 months), the UPDRS Part III score (hazard ratio, 1.09 [95% CI, 1.06-1.13] for 1 scale unit change per 6 months), and the Schwab and England Independence Scale score (hazard ratio, 1.29 [95% CI, 1.12-1.48] for 5 percentage point change per 6 months) was associated with earlier need for symptomatic therapy. AND RELEVANCE In early PD, the UPDRS Part II score and Part III score and the Schwab and England Independence Scale score can be used to measure disease progression, whereas the 39-item Parkinson's Disease Questionnaire and summary index, Total Functional Capacity scale, and the 12-item Short Form Health Survey Physical Summary and Mental Summary are not sensitive to change. clinicaltrials.gov Identifiers: NCT00063193 and NCT00076492.